2008
DOI: 10.1111/j.1750-3841.2008.00893.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Asparagus Lignin by HPLC

Abstract: Lignin is the cell wall component most frequently associated with hardening. Its characterization and quantification are very important to understand the biochemical modifications related to the changes in texture of vegetables such as asparagus (Asparagus officinalis), in which this organoleptic attribute is a very important quality factor. In this study, asparagus lignin from the basal sections of fresh and stored spears was analyzed using 2 methods, the traditional (Klason lignin) and the recently developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…In white asparagus, so far the focus has been on the total phenolic content [96] and specifically, ferulic acid derivatives [65,102]. Here, it was shown that an increased level of ferulic acids is associated with post-harvest spear hardening [65], and that post-harvest storage temperature plays an important role in cell wall hardening [4,6,102,103].…”
Section: Cultivation Harvesting and Storage Influences On Asparagusmentioning
confidence: 93%
See 1 more Smart Citation
“…In white asparagus, so far the focus has been on the total phenolic content [96] and specifically, ferulic acid derivatives [65,102]. Here, it was shown that an increased level of ferulic acids is associated with post-harvest spear hardening [65], and that post-harvest storage temperature plays an important role in cell wall hardening [4,6,102,103].…”
Section: Cultivation Harvesting and Storage Influences On Asparagusmentioning
confidence: 93%
“…Harvesting has a direct impact on the metabolism of plant materials, as it can lead to the activation of plant defence and stress mechanisms and eventually senescence and decay, leading to the production of several protective secondary (volatile and non-volatile) metabolites and proteins [101]. The impact of cultivation conditions, harvesting and storage of asparagus on its antioxidant capacity have been thoroughly examined [14,64,65,96,102,103]. In white asparagus, so far the focus has been on the total phenolic content [96] and specifically, ferulic acid derivatives [65,102].…”
Section: Cultivation Harvesting and Storage Influences On Asparagusmentioning
confidence: 99%
“…The estimation of lignin composition has been made through different methods: pyrolysis–gas chromatography–mass spectrometry (Py-GC/MS) (Klap et al, 2000), nuclear magnetic resonance (NMR) (Jin et al, 2007; Weng et al, 2010; Marques et al, 2016; Reyes-Rivera et al, 2018), Fourier transform infrared (FTIR) (Li et al, 2015; Reyes-Rivera et al, 2015; Reyes-Rivera et al, 2018), and high-performance liquid chromatography (HPLC) (Jaramillo-Carmona et al, 2008; Kline et al, 2010; Reyes-Rivera et al, 2015). For this reason, in this paper, Klason lignin is used directly to perform infrared (FTIR) spectrum readings, due to Reyes-Rivera et al (2018) finding consistent values when comparing these with other methods such as Py-GC/MS and NMR.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the effect of extrusion processing on lignin content, an increase (35.32%) was detected only in CC extruded at 100°C with the expansion screw configuration ( Table 2). The cross-linked structure of lignin polymers makes it a highly insoluble material, where small fractions are solubilized by chemical treatments (Jaramillo-Carmona et al 2008). In the case of WSC samples, extrusion did not affect the content of soluble lignin.…”
Section: Ligninmentioning
confidence: 99%